Penentuan Kadar Sulfat pada Air Sumur di Wilayah Surabaya Menggunakan Spektrofotometer - Agustiani, Elly; Triastuti, Warlinda Eka; Sampurno, Ade Citra Oktaviana Elok; Zahrah, Hanifah Fauziyah; Tyas, Sunia Rahma Cahyaning; Santoso, Yustia Dwi Fitria; Rahmawati, Affy Milatur; Martasari, Amelia; Wintara, Ellen Septia; Amali, Hafid (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The quality of drinking water can be assessed based on three aspects: physical, chemical, and microbiological aspects. One of the chemical aspects in determining water quality is the sulfate content. UV-Vis spectrophotometry method has been widely used to analyze sulfate content. UV-Vis spectrophotometry is a spectroscopic analysis technique that uses an electromagnetic wave source with ultraviolet (UV) for wavelength (190-380 nm) and visible light with wavelength (380-780 nm). The purpose of this study is to determine the absorbance and concentration of samples using spectrophotometric analysis, calculate the sulfate content in the samples, and compare it with the Indonesian Ministry of Health Regulation Permenkes RI No. 32//2017. The research stages include calibration, calibration curve creation, making standard H2SO4 solutions, measuring the absorbance of the standard solutions, and analyzing the sulfate content in water samples. The research results showed that the sulfate concentration in the Bangkalan, Nginden, Sidoarjo, Keputih, and Kapas Madya well water samples were 14.0817, 27.551, 29.1837, 49.0817, 54.6939 ppm, respectively. Based on the Indonesian Ministry of Health Regulation Permenkes RI No. 32//2017, the maximum sulfate content in water is 400 mg/L, thus it can be concluded that the water samples in those areas have met the clean water standards.